2015
DOI: 10.1167/15.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cognitive mechanisms involved in the processing of single objects and object ensembles

Abstract: Behavioral research has demonstrated that the shape and texture of single objects can be processed independently. Similarly, neuroimaging results have shown that an object's shape and texture are processed in distinct brain regions with shape in the lateral occipital area and texture in parahippocampal cortex. Meanwhile, objects are not always seen in isolation and are often grouped together as an ensemble. We recently showed that the processing of ensembles also involves parahippocampal cortex and that the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
(69 reference statements)
2
14
1
Order By: Relevance
“…Interestingly, this ability comes at the expense of losing the ability to provide fine details about the individual objects in the ensemble (e.g., Alvarez & Oliva, 2008;Chong & Treisman, 2003;Ariely, 2001;Parkes, Lund, Angelucci, Solomon, & Morgan, 2001;Watamaniuk & Duchon, 1992;Williams & Sekuler, 1984). This demonstrates that there is a tradeoff across these different visual perceptual processes, and consistent with this notion, we have recently demonstrated that there may be different underlying cognitive mechanisms supporting single-object versus object ensemble perception (Cant, Sun, & Xu, 2015).…”
Section: Introductionsupporting
confidence: 66%
“…Interestingly, this ability comes at the expense of losing the ability to provide fine details about the individual objects in the ensemble (e.g., Alvarez & Oliva, 2008;Chong & Treisman, 2003;Ariely, 2001;Parkes, Lund, Angelucci, Solomon, & Morgan, 2001;Watamaniuk & Duchon, 1992;Williams & Sekuler, 1984). This demonstrates that there is a tradeoff across these different visual perceptual processes, and consistent with this notion, we have recently demonstrated that there may be different underlying cognitive mechanisms supporting single-object versus object ensemble perception (Cant, Sun, & Xu, 2015).…”
Section: Introductionsupporting
confidence: 66%
“…Much behavioral evidence has been accumulated supporting this notion 6,7,1115,21,99103, but see 104 , although only a few recent fMRI studies have compared the neural representations of ensemble coding and individual processing 105107 . Cant and Xu 105,106 showed that PPA and LO were preferentially engaged in texture perception and object processing, respectively; and Huis in’t Veld and de Gelder 107 showed the greater anticipatory and action preparation activity in the areas including IPL, SPL, SFG, and premotor cortex for interactive body movement of a group of panicked people, compared to an unrelated movement of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Different patterns of hemispheric lateralization for the crowd emotion vs. individual emotion processing suggest that they may rely on qualitatively distinct systems. Much behavioral evidence has been accumulated supporting this notion (e.g., Alvarez & Oliva, 2008;Ariely, 2001;Cant, Sun, & Xu, 2015;Chong et al, 2008;Chong & Evans, 2011;Chong & Treisman, 2005;Choo & Franconeri, 2010;Corbett & Oriet, 2011;Haberman, Brady, & Alvarez, 2015;Haberman & Whitney, 2010;Im & Halberda, 2013;Leib et al, 2012;Parkes et al, 2001, but see Myczek & Simons, 2008, although only a few recent fMRI studies have compared the neural representations of ensemble coding and individual processing (e.g., , 2017Huis in't Veld & de Gelder, 2015). Xu (2015, 2017) showed that PPA and LO were preferentially engaged in texture perception and object processing, respectively; and Huis in't Veld and de Gelder (2015) showed the greater anticipatory and action preparation activity in the areas including IPL, SPL, SFG, and premotor cortex for interactive body movement of a group of panicked people, compared to an unrelated movement of individuals.…”
Section: Discussionmentioning
confidence: 99%